Angiographic classification of patterns of restenosis following femoropopliteal artery intervention: A proposed scoring system. Issue 4 (10th August 2017) - Garcia, Lawrence A.; Rocha‐Singh, Krishna J.; Krishnan, Prakash; Zeller, Thomas; Tepe, Gunnar; Fleming, Mark; Granada, Juan F.; Turco, Mark A.; Tieché, Christopher; Jaff, Michael R.
Abstract: Objectives: To propose a classification system for characterizing angiographic femoropopliteal artery restenosis patterns associated with common endovascular modalities. Background: Peripheral artery disease is a worldwide issue affecting millions of people. Despite a myriad of endovascular technologies available to treat peripheral artery disease of the femoropopliteal arteries, restenosis remains a common failure mode. Characterizing common patterns of restenosis is important to discern the potential impact of baseline patient, lesion, and procedural characteristics, as well as treatment modalities on either the primary success or the failure patterns associated with restenosis. Methods: Studies included in the analysis were from previous core laboratory‐adjudicated femoropopliteal artery disease trials and registries reflecting a wide array of treatment modalities. Results: From the subjects enrolled and analyzed, there were 403 total angiograms for analysis and adjudication. Target lesion revascularization images of the 32 validation cases were evaluated for index treated length, diameter stenosis, and lesion morphology characteristics. The following lesion types are proposed: Type 1 "Focal" pattern, which may be "Edge Proximal" or "Edge Distal" depending on location; a Type 2 "Multifocal" pattern which may also exhibit edge restenosis, but may also be "Edge Bilateral"; a Type 3 "Moderate" pattern and a Type 4 "Diffuse" pattern; and finally, a Type 5 "Occlusion". Conclusions: A classification system that enables healthcare professionals to anticipate and describe failures following the index procedure, thereby impacting the choice of options for retreatment, may facilitate consistency and standardization within the heterogeneous field of endovascular device treatments for the femoropopliteal artery.